In-situ removal of odorous NH3 and H2S by loess modified with biologically stabilized leachate. (1st December 2022) - Chen, Junlan; Wang, Yujing; Shao, Liming; Lü, Fan; Zhang, Hua; He, Pinjing
Abstract: The loess regions distribute widely in Northwestern China, North America and Eastern Europe. For these regions, landfill is a suitable technology for solid waste treatment. However, as a landfill cover material, loess is not very effective in controlling the emission of malodorous gases. The present study modified loess with biologically stabilized leachate, and investigated the capacities and mechanisms of the modified loess to remove odorous NH3 and H2 S. The removal rates of NH3 and H2 S at different acclimation time, targeted gas concentrations and temperatures were measured. It was found that the NH3 removal rate of the modified loess was up to 0.08 μmol/(g·hr), which was 1.8 times that of the virgin loess. The H2 S removal rate of the modified loess was up to 1.74 μmol/(g·hr), which was 1.25 times that of the virgin loess. The half-meter loess layer modified by biologically stabilized leachate achieved nearly 100% removal of H2 S. The improvement of NH3 and H2 S removal ability was mainly due to the enrichment of relevant microorganisms. This work proposed a novel method for in-situ control of malodorous pollutants in landfills in the loess regions, and proved that the in-situ removal of NH3 and H2 S using the loess modified with biologically stabilized leachate is feasible and cost-effective. Graphical abstract: Image 1 Highlights : An in-situ odor control method for landfills in loess regions was proposed. Loess was modified with biologically stabilized leachate for landfill cover. Microbes and functional genes for odor control were enriched after modification. The highest NH3 removal rate of loess was increased by 80% after modification. The highest H2 S removal rate of loess was increased by 25% after modification.